2014
DOI: 10.3109/14992027.2014.938782
|View full text |Cite
|
Sign up to set email alerts
|

‘Getting used to’ hearing aids from the perspective of adult hearing-aid users

Abstract: Getting used to hearing aids is a challenging multi-factorial process with both psychosocial and practical difficulties besides demands of adjusting to hearing-aid input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…A 2010 MarkeTrack survey found that characteristics of the hearing healthcare professional (including knowledge, professionalism, empathy, creation of realistic expectations and explanations about maintenance of hearing aids) and patient ratings of the quality of the fitting process were positively correlated with patients' hearing aid use, benefit and satisfaction (Kochkin et al 2010). Qualitative studies reported that patients value interaction with their audiologists and that interaction with audiologists may help patients get used to using hearing aids (Dawes, Maslin, and Munro 2014) and motivated patients to use their hearing aids (Aazh 2016b). A systematic review of determinants of hearing aid outcomes highlighted the need to explore the dynamics of the patient-hearing healthcare professionals clinical interactions to facilitate patient outcomes (Knudsen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A 2010 MarkeTrack survey found that characteristics of the hearing healthcare professional (including knowledge, professionalism, empathy, creation of realistic expectations and explanations about maintenance of hearing aids) and patient ratings of the quality of the fitting process were positively correlated with patients' hearing aid use, benefit and satisfaction (Kochkin et al 2010). Qualitative studies reported that patients value interaction with their audiologists and that interaction with audiologists may help patients get used to using hearing aids (Dawes, Maslin, and Munro 2014) and motivated patients to use their hearing aids (Aazh 2016b). A systematic review of determinants of hearing aid outcomes highlighted the need to explore the dynamics of the patient-hearing healthcare professionals clinical interactions to facilitate patient outcomes (Knudsen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…'getting used to' hearing aids (Dawes, Maslin, et al 2014 masking') has a significant impact on speech recognition, and that attention plays a 116 key role in resistance to distraction effects (for example, Helfer & Freyman, 2008).…”
mentioning
confidence: 99%
“…This could potentially decrease the amount of loud noise and improve speech intelligibility in a social setting. Furthermore, if listeners are novice hearing aid wearers, it may be important to remind them that normal hearing individuals also experience difficulty understanding speech in loud noise, and that environmental noise may become more acceptable with continued hearing aid usage (Dillon, 2001;Philibert et al, 2005;Dawes et al, 2014;Kuk et al, 2015). The current study did not find a relationship between TNL and overall hearing aid satisfaction.…”
Section: Predicting Hearing Aid Satisfactionmentioning
confidence: 52%